Analisis Pengaruh Sektor Pariwisata Terhadap Pertumbuhan Ekonomi di Kota Bandung - Hol, Anna Raischell; Zhafirah, Rhevaira Kayla; Ritonga, Dizka Angel Naomi; Subekti, Eka Wulandari Nur; Desmawan, Deris (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
This research was conducted to analyze how the tourism sector influences economic growth in the city of Bandung, West Java in the period 2014 to 2023. The analysis method uses multiple linear regression by maximizing the SPSS 25 program with a quantitative approach. Data obtained via BPS Bandung City and West Java Open Data. This research shows that the tourism sector, namely the restaurant sector, has a positive and significant effect on the economic growth of the city of Bandung, which means that if the number of restaurants increases, economic growth will increase. Meanwhile, the number of tourists and the hotel sector have a positive but not significant effect on the economic growth of the city of Bandung. This shows that it is necessary to increase the number of tourists and the number of hotels to increase the economic growth of the city of Bandung.”